PLEASE SOLVE THE QUESTION
Attachments:
![](https://hi-static.z-dn.net/files/df5/f8bf806fdab205eacc7b83852f07bd75.jpg)
Answers
Answered by
7
Proof by using Pythagoras theorem :
In Δ ADC ,
AD² = AC² + DC²
⇒ DC² = AD² - AC² ,,,,,,,,,,,,, ( 1 )
In Δ ABC ,
AB² = BC² + AC²
⇒ AB² = ( 2 DC )² + AC²
⇒ AB² = 4 DC² + AC²
⇒ AB² = 4 ( AD² - AC² ) + AC²[ from 1 ]
⇒ AB² = 4 AD² - 3 AC²
Answered by
0
hi
here is your answer
hope it helps
plz mark brainliest
Attachments:
![](https://hi-static.z-dn.net/files/d77/1ec765a95624a761428f267db9d4d9a8.jpg)
Similar questions